2015
DOI: 10.1167/iovs.15-16587
|View full text |Cite
|
Sign up to set email alerts
|

Functional Impact of Collagens on the Activity Directed by the Promoter of theα5Integrin Subunit Gene in Corneal Epithelial Cells

Abstract: Collagens considerably suppressed α5 gene expression in CECs, suggesting that during wound healing, they may interfere with the influence FN exerts on CECs by altering their adhesive and migratory properties through a mechanism involving a reduction in α5 gene expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 85 publications
0
13
0
Order By: Relevance
“…ITGA5 has been widely accepted as involved in the process of invasiveness and tumorigenesis [20,32]. In our research, the expression level of ITGA5 in SiITGA5 group was down-regulated at both mRNA and protein levels, which means that ITGA5 might work as a facilitator in GBM.…”
Section: Discussionmentioning
confidence: 51%
“…ITGA5 has been widely accepted as involved in the process of invasiveness and tumorigenesis [20,32]. In our research, the expression level of ITGA5 in SiITGA5 group was down-regulated at both mRNA and protein levels, which means that ITGA5 might work as a facilitator in GBM.…”
Section: Discussionmentioning
confidence: 51%
“…However, none of them have been done in the context of human wound healing of the cornea. The proximal element identified in our study (-82/-203) bears target sites for TBP (TATA-binding protein), AP-1 and both the Sp1 and Sp3 family members (Figure 3A), which we are very familiar with [11,17,18,53,66]. We demonstrated that CLU gene transcription was indeed ensured in part by the binding of the TFs Sp1/Sp3 and AP-1 to overlapping target sites within the basal promoter segment CLU -203/-153.…”
Section: Discussionmentioning
confidence: 85%
“…The significant reduction in the formation of both the AP-1 and Sp1/Sp3 complexes combined to the formation of new, slow-migrating supershifted complexes (SSC) upon addition of a polyclonal antibody that recognizes AP-1 (lane 3), Sp1 (lane 4), or the combination of both Sp1 and Sp3 (lane 5), provided evidence that formation of complexes b and a/c resulted from the recognition of the CLU-203/-/53 labeled probe by AP-1 and Sp1/Sp3, respectively (Figure 4D). Formation of complex d results from the recognition of the labeled probe by non-specific DNA binding proteins, as is often observed in EMSA [17,18,[52][53][54][55][56][57].…”
Section: Members From the Ap1 And Sp1 Families Bind To The Clu Basal Promoter In Hcecsmentioning
confidence: 94%
See 1 more Smart Citation
“…Some of these key target genes have been shown to play a role in EC in previous studies. As an integrin α subunit, ITGA5 is involved in invasiveness and tumorigenesis (20,21) and is one of the most abundant proteins in the extracellular matrix. Numerous studies have shown that ITGA5 could have a regulatory role in specific cancers by activating focal adhesion kinases to promote cell adhesion and migration (21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%